Functional ingredients produced by culture of Koliella antarctica - FOGLIANO V; MARTELLO A; CAIAZZO M; LOBOSCO O; FORMISANO F; CARLINO P. A; MECA G; GRAZIANI G; DI MARTINO RIGANO V; VONA V; CARFAGNA S; RIGANO C.; et al. (Aquaculture, 2010)
Unicellular algae represent an interesting source of bioactive food ingredients. In this study, fatty acids and carotenoids of Koliella antarctica, a psychrophylic Antarctic unicellular alga, were investigated. K. antarctica was cultivated at different temperatures and harvested at the early exponential growth phase and at the late exponential growth phase. After 240 h, at the end of the late exponential growth phase, the cell biomass concentration was 1.1 g L−1 at 10 °C while it was 2.2 g L−1 at 15 °C. The lipid profile of K. antarctica was rich in polyunsaturated fatty acids (PUFA) particularly at the early exponential phase (50.8% of total fatty acids). The comparison of data obtained from algae cultivated at 10 °C and 15 °C, showed at 15 °C a strong increase in saturated lipids and a decrease in PUFA. At the same time the presence of EPA and DHA was marginally affected, with a percentage decrease around 15–20%. The productivity of EPA and DHA was similar at the two growth temperatures with maximum values of 0.6 mg L−1 day−1 and 1.3 mg L−1 day−1, at 10 and 15 °C, respectively. In K. antarctica cultures, the concentration of lutein and astaxanthin increased during growth up to 1.4 g per 100 g dry weight for both compounds. This is one of the highest concentrations reported in the literature for carotenoid production by unicellular algae, with a total carotenoid productivity of 3.1 mg L−1 day−1. Although optimization studies to increase K. antarctica biomass production were not yet carried out, data suggested that this alga is a promising source for low cost production of valuable bioactive compounds. The performance recorded at 15 °C suggested that it could be particularly suitable for outdoor cultivation during the winter season in the Mediterranean region.